2021
DOI: 10.2478/hukin-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

Post-Eccentric Flywheel Underwater Undulatory Swimming Potentiation in Competitive Swimmers

Abstract: Underwater undulatory swimming (UUS) influences overall swimming performance, therefore swimmers should try to maximize it. This research aimed to: 1) assess the effects of an activation protocol based on post-activation performance enhancements upon UUS; and 2) evaluate the differences between males and females. Seventeen competitive swimmers (male = 10; female = 7) participated in a cross-sectional study designed to test performance in UUS at 10 m after a traditional swimming warm-up (TRA) and after adding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…However, strength training can reduce the tumble turn time in contrast with endurance or concurrent training [15]. Additionally, acute effects obtained with protocols such as PAPE (post-activation performance enhancement) have positive effects on turn performance with an increase in the UUS (underwater undulatory swimming) kinetic variables [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, strength training can reduce the tumble turn time in contrast with endurance or concurrent training [15]. Additionally, acute effects obtained with protocols such as PAPE (post-activation performance enhancement) have positive effects on turn performance with an increase in the UUS (underwater undulatory swimming) kinetic variables [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fig 1 illustrates the schematisation of the study selection process. Initially, 317 records were identified and 25 [ 1 , 4 7 , 16 , 19 , 21 , 33 – 49 ] studies were included in this review. These studies reported the mean and standard deviation or confidence interval for at least one primary outcome variable.…”
Section: Resultsmentioning
confidence: 99%
“…Upper limb and combined upper and lower limb PAPE protocols demonstrated mostly unfavourable swim performance changes [ 34 , 35 , 38 , 40 , 46 ]. Lower-limb only PAPE using plyometric actions have demonstrated mixed results [ 7 , 39 , 43 ], though the use of heavier loaded conditions using band resisted squats or loaded lunge and squats have consistently improved time to 15 m [ 7 , 36 , 40 ], dive kinetics [ 37 ], and the underwater kick phase [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations